2023
DOI: 10.18559/ref.2022.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Economic openness, institutional quality and per capita income: Evidence from the Economic Community of West African States (ECOWAS)

Abstract: The controversy surrounding the actual impact of institutional quality and economic openness on economic growth is among the motivating factors for this study. The study seeks to investi- gate this relationship in the Economic Community of West African States (ECOWAS) by using the panel autoregressive distributed lag (ARDL) test with annual series covering the period from 2000 to 2020. Findings indicate that in the short-run, regulatory quality and FDI outflows had an adverse impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In another vein, Wang et al, (2021) showed that institutional quality promoted economic growth in non-oil producing countries, but showed no significant impact in oil-producing countries. In a study for the Economic Community of West African Countries (ECOWAS), Nzeh et al, (2022) revealed that regulatory quality and FDI outflows impacted adversely on the economy of the bloc in the short-run. On the other hand, while trade openness, political stability and FDI outflows had negative impact on the economy in the long-run, the impact of regulatory quality was positive.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In another vein, Wang et al, (2021) showed that institutional quality promoted economic growth in non-oil producing countries, but showed no significant impact in oil-producing countries. In a study for the Economic Community of West African Countries (ECOWAS), Nzeh et al, (2022) revealed that regulatory quality and FDI outflows impacted adversely on the economy of the bloc in the short-run. On the other hand, while trade openness, political stability and FDI outflows had negative impact on the economy in the long-run, the impact of regulatory quality was positive.…”
Section: Empirical Literaturementioning
confidence: 99%